Developing a Logarithmic Chinese Reading Acuity Chart - Han, Q. M.; Cong, L. J.; C. Yu; L. Liu (Optometry and Vision Science, 2017)
PURPOSE: An individual's reading ability cannot be reliably predicted from his/her letter acuity, contrast sensitivity, and visual field extent. We developed a set of Chinese reading acuity charts (C-READ) to assess the reading ability of Chinese readers, based on the collective wisdom of previously published reading acuity charts, especially the MNRead and the Radner Reading Charts. METHODS: The C-READ consists of three charts. Each consists sixteen 12-character simplified Chinese sentences crafted from first- to third-grade textbooks. One hundred eighteen native Chinese-speaking college students (aged 22.1 +/- 2.1 years) with normal or corrected to normal near vision (-0.26 +/- 0.05 logMAR) were included in the study to develop the C-READ charts, to test the homogeneity of the three charts, and to validate the C-READ against the text paragraphs from the International Reading Speed Texts (IReST) with corrected and uncorrected near vision. RESULTS: The reading acuity, critical print size, and maximum reading speed for young normal native Chinese-speaking readers were 0.16 +/- 0.05 logMAR, 0.24 +/- 0.06 logMAR, and 273.44 +/- 34.37 characters per minute (mean +/- SD), respectively. The reliability test revealed no significant differences among the three C-READ charts and no significant test order effect in the three reading parameters. Regression analyses showed that the IReST reading speed could be reliably predicted by the C-READ maximum reading speed under the corrected near-vision condition (adjusted R = 0.72) and by C-READ maximum reading speed and critical print size under the uncorrected near-vision condition (adjusted R = 0.69). CONCLUSIONS: The three C-READ charts are very comparable to each other, and there is no significant order effect. Reading test results can accurately predict continuous text reading performance quantified by the IReST reading speed over a wide range of refractive errors. The C-READ is a reliable and valid clinical instrument for quantifying reading performance in simplified Chinese readers.
Keywords: *Reading; Female; Humans; Language; Male; Reproducibility of Results; Translations; Vision Disorders/*diagnosis/physiopathology; Vision Tests/*methods; Visual Acuity/*physiology; Young Adult